DNA methylation: organ specific variations in the methylation pattern within and around ovalbumin and other chicken genes. - Mandel, J L (1979)
The restriction enzymes HhaI and HpaII, whose activity is inhibited by cytosine methylation within their recognition sites, have been utilised as probes to study methylation in the vicinity of the ovalbumin gene in DNA from various chicken tissues. This was complemented by a preliminary study of methylation in the regions of chicken ovotransferrin (conalbumin), ovomucoid and beta-globin genes. From our data we conclude that HaI or HpaII sites can be divided in 3 classes according to their pattern of methylation in different tissues. In the first class of sites (mV class) the extent of methylation varies in different tissues. The patterns obtained show that methylation at the sites located within and around the 3 genes which code for egg white proteins is in general lowest in oviduct of laying hen, where these genes are expressed. However some sites are not methylated (m- class) and others are 95 to 100% resistant (m+ class) to digestion by HhaI or HpaII in the DNAs of all the tissues which were tested. Our study has also revealed a remarkable number of allelic variants for the presence of HhaI or HpaII sites in the region of the ovalbumin gene.